Delayed diagnosis of basilar artery occlusion in a 28-year-old postpartum woman - Alyssa Dwight; Daniela Fishbein; Jonathan Davidow; Robert N. Sawyer; Mohamed Tiouririne (BMC Neurology)
Abstract Background Basilar artery strokes, which are often challenging to diagnose due to their diverse symptoms and uncommon occurrence, demand timely identification to mitigate severe consequences. Case presentation This case report discusses a 28-year-old woman who was admitted 7 months postpartum for suspected status epilepticus. Her initial presentation of convulsive activity and encephalopathy prompted an initial differential diagnosis including toxin-related seizures, encephalitis, and serotonin syndrome among others. A CT angiogram revealed nonocclusive basilar artery thrombosis and hypodensities in the basal ganglia and thalamus. MRI revealed additional strokes in the PCA and SCA territories. Conclusions The patient’s age and recent history of preeclampsia during pregnancy prompted pertinent discussions regarding pregnancy-related strokes. Most importantly, this case sheds light on the diverse presentations of basilar artery strokes and stresses the urgency of swift identification using imaging to avoid significant morbidity and mortality.